Islamic Law and Medical Ethics of Female Circumcision Practices - Trisna Wati, Ika (Journal Of Gender, Child And Humanity Studies, 2025)
The practice of female circumcision continues to provoke complex debates, intersecting the domains of Islamic law, medical ethics, and cultural traditions. This article critically examines the practice by exploring the diverse interpretations of Islamic legal texts regarding female circumcision and medical perspective. Simultaneously, it evaluates the medical implications of the practice. By integrating these perspectives, the study aims to illuminate pathways for reconciling religious beliefs with contemporary ethical and medical principles. This approach seeks to contribute to informed discourse, promoting a balance between religious understanding and human rights advocacy in addressing female circumcision practices.